THE EFFECT OF STORYBOARD TECHNIQUE ON STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT AT THE TENTH GRADE OF SMAN 2 KS CILEGON - LISA HIDAYANTI; JOHN PAHAMZAH; Delsa Miranty (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2020)
The objective of the study was to find out the effect of using storyboard technique on students’ reading comprehension in narrative text at the tenth grade of SMAN 2 Krakatau Steel Cilegon. The researcher used quantitative approach by implementing true experimental design. The sample of the research were 36 students in 10 MIA 3 as experimental group and 36 students in 10 MIA 4 as control group which selected through cluster random sampling. The storyboard technique, that is used as the treatment was administrated for the experimental group. The instrument in collected the data were pre-test and post-test. The result of independent t-test computation of post-test score showed that t count was more than the t table (6.274> 1.994). Based on the data analysis score, the Ho (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted. In other words, there was an effect of using storyboard technique on students’ reading comprehension in narrative text at the tenth grade of SMAN 2 KS Cilegon.